Poultry Ingredient Knowledge and Cooking Techniques as Predictors of Main Course Preparation Skills in Culinary Vocational Students - Nadiya Nurdiani; Mauren Gita Miranti; Lucia Tri Pangesthi; Andika Kuncoro Widagdo (INSPIRETECH GLOBAL INSIGHT, 2026)
This study aimed to analyze the predictive role of students' knowledge of poultry ingredients and cooking techniques on their main course preparation skills in the context of continental cuisine. A quantitative ex post facto design was employed with 35 eleventh-grade students from the Culinary Arts program at SMKN 3 Kediri, Indonesia, selected via purposive sampling from a population of 152 students. Data were collected using validated multiple-choice tests measuring poultry ingredient knowledge (X1) and cooking technique knowledge (X2), alongside a performance assessment rubric for main course preparation skills (Y). Instrument reliability was confirmed by Cronbach's alpha values of 0.938 and 0.702, respectively. Data were analyzed through descriptive statistics and multiple linear regression using SPSS version 25.0. Both independent variables demonstrated statistically significant partial effects on main course preparation skills (X1: t = 6.308, p < 0.001; X2: t = 5.732, p < 0.001). Simultaneously, the two predictors explained 62.2% of the variance in skill outcomes (Adjusted R² = 0.622; F = 7.548, p < 0.001). Poultry ingredient knowledge (β = 0.426) showed a slightly stronger predictive contribution than cooking technique knowledge (β = 0.386). Poultry ingredient knowledge and cooking technique knowledge are significant predictors of main course preparation skills in culinary vocational students. These findings highlight the critical role of theoretical content mastery in supporting psychomotor skill development and underscore the need for integrated theory-practice curricula in vocational culinary education.